Dampak Era Globalisasi Ekonomi terhadap Usaha Ternak Sapi Perah: Kajian Peluang, Kendala dan Strategi Pengembangan - Made Oka Adnyana; Sudi Mardianto (Jurnal Agro Ekonomi, 1996)
Free market and international investment in the global economic environment will also influence milk cow business in Indonesia especially farmers that mostly use imported component of feed. Meanwhile, price of milk in the world market tend to decline due to reduction of import tariff policy imposed by the goverment. Only efficient production system that can increase the competitiveness of lndonesia milk cow business in the world market. Otherwise, the volume of import will continuously increases. This study is aimed to investigate the competitiveness, constraints and prospect as well as the development strategies of milk cow business in Indonesia. A case study has been conducted in East Java. Financially, milk cow business in East Java has benefited farmers with return and cost ratio (R/C = 1.43). A policy to push milk production may be considered to meet the domestic demand or at least partially substitute the imported milk. This optimism is indicated by the domestic resource cost ratio (DRCR = 0.813 ). On the other hand, the impact of price policy on input and output and market distortion exist in this agribusiness has clearly provide economic incentive to the farmers to increase their milk production. This circumstances indicated by an indicator of effective protection coefficient (EPC = 1,4499). In other world about 45 percent of added value will be distributed to farmers. By utilizing the domestic market potential, intensive insemination program and increase of business efficiency, the milk industry in Indonesia has a very prospective future. However, monopsony market structure, very weak farmer's capital position, and unwell insemination program implementation among production areas are become a set of constraints that need policy action to increase the performance of milk cow business in Indonesia. Thus, the future development strategies needed are: (1) increase the quality and productivity via technology improvement especially feed and business management. In the short run, deregulation on the other hand, particularly market structure must be taken into action.